A Study on Parallel Computation Tools on Networked PCs - Suhartanto, Heru (Makara Journal of Technology, 2006)
A Study on Parallel Computation Tools on Networked PCs. Many models for natural phenomena, engineering applications and industries need powerfull computing resources to solve their problems. High Performance Computing resources were introduced by many researchers. This comes in the form of Supercomputers and with operating systems and tools for development such as parallel compiler and its library. However, these resources are expensive for the investation and maintenance, hence people need some alternatives. Many people then introduced parallel distributed computing by using available computing resource such as PCs. Each of these PCs is treated as a processors, hence the cluster of the PC behaves as Multiprocessors Computer. Many tools are developed for such purposes. This paper studies the peformance of the currently popular tools such as Parallel Virta\ual Machine (PVM), Message Passing Interface (MPI), Java Remote Method Invocation (RMI) and Java Common Object Request Broker Architecture (CORBA). Some experiments were conducted on a cluster of PCs, the results show significant speed up. Each of those tools are identified suitable for a certain implementation and programming purposes.